THE INFLUENCE OF STUDENT ENGAGEMENT AND TEACHERS' PERFORMANCE TO STUDENTS' SATISFACTION IN PUBLIC SENIOR HIGH SCHOOLS IN BANDUNG (INDONESIA) - Heisi, Mahase (2014)
Students are direct receivers and participators for education service, and their study activities wouldinfluence their perceptions and satisfactions to the educational quality. Through studying on the influence of students' engagement and teachers' performance to students' satisfaction, in this article, the researcher aimed at studying the influence of these variables to student satisfaction in Public Senior High Schools in Bandung (SMAN). It obvious that some students showed or reported a certain level of dissatisfaction in their learning. Therefore, it was important to explore the level of influence of student engagement and teachers' performance to student satisfaction. The general objective of this study is to explore and check the influence of student engagement and teachers' performance to students' satisfaction in Public Senior High Schools in the city of Bandung in Indonesia. This research used quantitative research methodology (descriptive) which was conducted at Public senior high schools in Bandung. The population consists of twenty nine (29) schools and sampling consisted of five schools which were taken from different regions (North, South, East, West and central) of the city of Bandung. Each school was given copies of questionnaires. The measurement of the influence of student engagement and teachers' performance to student satisfaction was done with Likert scale with five weighted options. The findings showed that influence of student engagement and teachers' performance to student satisfaction is good enough in these schools. It was found that contribution madeby thestudent engagement and teachers'performance onstudent satisfactionisstrong enough. While the remainingpartbelongs toother factorsthataffectstudent satisfaction which were not examinedby the researcher. On the same hand student engagement had good influence. Whileteachers performance tosatisfaction ofthe students had also had the same good influence. Therefore, the influence of student engagement and teachers' performance to student satisfaction is found to be good enough in these schools. This is positive in the process of learning but calls for attention from all stakeholders in educational administration. There is also a room for improvement. This research recommends that the future research be focused between public and private senior high schools